PENGARUH CITRA DESTINASI TERHADAP KEPUASAN DAN LOYALITAS WISATAWAN - Noval Monali; Hasanuddin Bua; Nursaban Rommy (Jurnal Manajemen, Bisnis dan Organisasi (JUMBO), 2019)
This study aims to: 1) Analyze the influence of destinations on tourist satisfaction, 2) Know and analyze the influence of destinations on tourist loyalty, 3) Analyze the influence of tourist satisfaction on tourist loyalty, 4) Analyze the influence of destination images on loyalty through satisfaction. The population of this study is foreign and national tourists visiting Wakatobi departing 2,287. sample size measurements using the Slovin formula with a precision of 6% thus the study sample compared 248 tourists. The method of collecting data using questionnaires, research data was analyzed using a structural model with the help of Amos 20 software.The results of the study: 1) the positive and significant destination image of tourist satisfaction, 2) positive and significant image of satisfaction, 3) positive image satisfaction and significant loyalty, 4) positive and significant destination image towards loyalty through satisfaction.Keywords: destination image , satisfaction, tourist loyalty